Human Resources Management - AD2345 - 202202 - Peña Cavassa, Viviana Hilda (2022)
Course Overview THIS IS A UNIVERSITY OF ARIZONA COURSE AND THE FOLLOWING IS A COPY OF THE ORIGINAL SYLLABUS FROM D2L FOR REFERENCE. From the smallest venture to the largest multinational conglomerate, at its core are people. We will explore the oftentimes complex and dynamic interactions between workers, organizations and the environments within which they operate. We will explore these interactions from a variety of perspectives. How might organizations create high-performance work systems that maximize their sustainable competitive advantage? How might individuals feel challenged in their work, while not feeling overwhelmed, creative but still supported and protected, confident and competent but still have opportunities to improve and grow? This course will explore historical trends and best practices in managing human resources by evaluating approaches adopted by actual organizations in a variety of industries and circumstances. Introduction to Human Resources Management is designed to provide you with an understanding of human resource (HR) management. In addition to providing you with knowledge of HR management issues addressed by most managers, we will examine these issues from a broader organizational perspective.